Abrogation of STAT3 signaling cascade by zerumbone inhibits proliferation and induces apoptosis in renal cell carcinoma xenograft mouse model - Shanmugam, M.; Rajendran, P.; Li, F.; Kim, C.; Sikka, S.; Siveen, K.; Kumar, Alan Prem; Ahn, K.; Sethi, G. (John Wiley and Sons Inc., 2015)
Persistent activation of signal transducer and activator of transcription 3 (STAT3) is one of the characteristic features of renal cell carcinoma (RCC) and often linked to its deregulated proliferation, survival, and angiogenesis. In the present report, we investigated whether zerumbone, a sesquiterpene, exerts its anticancer effect through modulation of STAT3 activation pathway. The pharmacological effect of zerumbone on STAT3 activation, associated protein kinases and phosphatase, and apoptosis was investigated using both RCC cell lines and xenograft mouse model. We observed that zerumbone suppressed STAT3 activation in a dose- and time-dependent manner in RCC cells. The suppression was mediated through the inhibition of activation of upstream kinases c-Src, Janus-activated kinase 1, and Janus-activated kinase 2. Pervanadate treatment reversed zerumbone-induced downregulation of STAT3, suggesting the involvement of a tyrosine phosphatase. Indeed, we found that zerumbone induced the expression of tyrosine phosphatase SHP-1 that correlated with its ability to inhibit STAT3 activation. Interestingly, deletion of SHP-1 gene by siRNA abolished the ability of zerumbone to inhibit STAT3 activation. The inhibition of STAT3 activation by zerumbone also caused the suppression of the gene products involved in proliferation, survival, and angiogenesis. Finally, when administered i.p., zerumbone inhibited STAT3 activation in tumor tissues and the growth of human RCC xenograft tumors in athymic nu/nu mice without any side effects. Overall, our results suggest for the first time that zerumbone is a novel blocker of STAT3 signaling cascade and thus has an enormous potential for the treatment of RCC and other solid tumors.